2016
DOI: 10.1111/bcp.13086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of statin therapy on plasma leptin concentrations: a systematic review and meta‐analysis of randomized placebo‐controlled trials

Abstract: Unless more consistent evidence becomes available in the future, the hypothesis of a relationship between statin use and serum leptin concentrations seem to be unfounded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
0
11
0
3
Order By: Relevance
“…They showed that simvastatin and simvastatin plus ezetimibe combination decreased the levels of adipokines. On the other hand, in a meta-analysis, statin therapy failed to show favorable effects on the leptin levels (42). Although our study is the first investi-gation that demonstrates the positive effects of rosuvastatin on the chemerin levels in patients with AMI, we think that there is a need for further large-scale studies.…”
Section: Discussionmentioning
confidence: 58%
“…They showed that simvastatin and simvastatin plus ezetimibe combination decreased the levels of adipokines. On the other hand, in a meta-analysis, statin therapy failed to show favorable effects on the leptin levels (42). Although our study is the first investi-gation that demonstrates the positive effects of rosuvastatin on the chemerin levels in patients with AMI, we think that there is a need for further large-scale studies.…”
Section: Discussionmentioning
confidence: 58%
“…The following search keywords and terms were used: ((statin * ) or ((“hydroxymethylglutaryl‐CoA reductase”) or (“HMGCoA reductase”) and (inhibitor * )) or (anticholesteremic) or (simvastatin) or (rosuvastatin * ) or (pravastatin * ) or (atorvastatin * ) or (fluvastatin * ) or (cerivastatin * ) or (pitavastatin * ) or (lovastatin * )) and ((ovary) or (ovarian)) and ((cancer) or (neoplasms) or (carcinoma) or (tumor)) and ((prognosis) or (outcome) or (survival) or (mortality) or (recurrence) or (progression) or (metastasis)). In addition, the reference lists of published narrative reviews were scanned to identify potential additional publications not retrieved by the manual search . In an effort to identify unpublished studies, the abstracts of the annual meetings up to 31 December 2017 of the related associations were also manually searched.…”
Section: Methodsmentioning
confidence: 99%
“…Another important issue is whether the medications for modifying vascular risk factors (e.g., antihypertensive, antihyperlipidemic, and antihyperglycemic agents) can decrease leptin levels. One systematic review for metaanalysis of randomized placebo-controlled trials (RCTs) focused on the impact of statin therapy on plasma leptin levels and showed that results are inconclusive [52]. Another meta-analysis of RCTs investigated the effects of pioglitazone on blood leptin levels in patients with T2DM and showed a significant difference, although relatively few RCTs were included, and a high level of statistical heterogeneity were found.…”
Section: Risk Factors Associated With the Severity Of Canmentioning
confidence: 99%